Pengaruh Model Pembelajaran Role Playing terhadap Hasil Belajar Siswa pada Pembelajaran Tematik Kelas IV SD pada gugus XVII Kota Bengkulu - Ribka Putri Kristina Hutauruk; Bambang Parmadie (Universitas Bengkulu, 2023)
The study aims to determine the influence of Role Playing learning models on thematic learning of student learning outcomes. This research is quantitative study. The research method used is an experimental Quasi with design of The Matching Only Pretest Posttest Control Group Design. The population was grade IV elementary school students in the XVII group of the city of Bengkulu. The sample was class IVA SDN 04 Bengkulu and IVB SDN 11 Bengkulu with total students as much as 56 people. The sampling technique uses purposive sampling. The research instrument used a Multiple Choices given through the pretest, posttest and observation sheet. The data analysis technique this study is quantitative analysis using descriptive statistics and inferential statistics . The hypothesis test on this study uses test-t. Based on the results of this study obtained t count of 7.61 with t tabel at a significant level of 5% by 2.01 where t count is greater than t_tabel with the details of the average value in Indonesian subjects is 85.35, the subject of IPS is 86.15 and PPKN is 84.54. Thus it can be concluded that there is a significant effect of student learning outcomes on Thematic learning using role playing models.